2006
DOI: 10.1007/s11912-006-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides and sezary syndrome: An update

Abstract: Mycosis fungoides (MF), and the associated leukemic variant Sezary Syndrome (SS), are the most common group of cutaneous T-cell lymphomas. MF/SS is a non-Hodgkin's lymphoma of mature, skin-homing, clonal, malignant T lymphocytes that initially presents in the skin as patches, plaques, tumors, or generalized erythema (erythroderma) and can involve the lymph nodes and peripheral blood. Much progress has been made in recent years in understanding the origin of the malignant T cell in MF/SS and the pathophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 67 publications
0
38
0
1
Order By: Relevance
“…12 There are many therapeutic options available for the management of CTCL, including MF/SS. 7,13 The choice of treatment is often determined by physician or patient preference, or institutional experience, particularly as there is a paucity of data from phase III trials and a lack of consensus concerning treatment for later stages of MF/SS. 3,[14][15][16] However, a number of authors have published recommendations or reviews on the management of CTCL, 1,3,7,15,17 , and guidelines have been published jointly by the British Association of Dermatologists and the UK Cutaneous Lymphoma Group.…”
Section: Introductionmentioning
confidence: 99%
“…12 There are many therapeutic options available for the management of CTCL, including MF/SS. 7,13 The choice of treatment is often determined by physician or patient preference, or institutional experience, particularly as there is a paucity of data from phase III trials and a lack of consensus concerning treatment for later stages of MF/SS. 3,[14][15][16] However, a number of authors have published recommendations or reviews on the management of CTCL, 1,3,7,15,17 , and guidelines have been published jointly by the British Association of Dermatologists and the UK Cutaneous Lymphoma Group.…”
Section: Introductionmentioning
confidence: 99%
“…27 Importantly, loss of CD7 expression is a hallmark of neoplastic T cells in MF. [28][29][30] Prior work demonstrated that loss of CD7 expression by MF cells in primary patient samples correlated with resistance to galectin-1-induced death. 30 However, we found that HH, a CD7 ϩ T-cell line derived from a patient with cutaneous T-cell lymphoma, was also resistant to galectin-1-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…11,26 Canine epitheliotropic lymphoma is a similar disease of older dogs that typically affects skin or mucus membranes and may have relatively slow (1-4 years) clinical progression. 16,20 The neoplastic cells are typically composed of CD8…”
mentioning
confidence: 99%